Improvement of the Civil Service Legislation in the Conditions of Power Restart in Ukraine: innovations and risks - Goncharuk, Natalia; Prudius, Lesia (My University, 2020)
The article is devoted to the study of innovations and risks of the amendments to the legislation on the civil service in the conditions of restarting power in Ukraine. It is established that the innovations relate to the scope of the Law of Ukraine “On Civil Service”, legal bases of the civil service, management of the civil service, entry into the civil service, its passage and suspension. In order to evaluate these innovations of the current Law on Civil Service of Ukraine, the method of SWOT analysis was applied. SWOT Analysis of the Civil Service Law of Ukraine allowed to identify the strengths anweaknesses of the internal environment of the changes and innovations that contribute to the improvement of the civil service legislation and cause threats and risks in the civil service, to identify as potential threats and the risks arising from the introduction of innovations, as well as the potential of the external environment to address them by further improving the civil service legislation to improve its quality and effectiveness and, adherence to European standards for the protection of human rights in the public service. Among the risks and threats of the changes were the following: substantial violations of the constitutional rights and freedoms of civil servants, discrimination and narrowing of their rights, violation of the Recommendations of the Committee of Ministers of the Council of Europe to the member states of the Council of Europe on the status of public servants in Europe Of Ukraine “On Civil Service”.
Keywords: державна служба; управління державною службою; законодавство про державну службу; порушення конституційних прав і свобод державних службовців